"Qoqnus"and "Phiniq" in "Nima's" and "Adonis's" Poetry - Reza Nazemiyan; Seddighe Horasfand; Yaqub Fooladi (ادبیات تطبیقی, 2018)
Ali Esfandiyari (Nima Youshij) and Ali Ahmad Saeed (Adonis) are among the eminent contemporary poets of Persian and Arabic literature, who had worked on mythology and symbolism. Phoenix, which is called "Qoqnus" in Persian and "Phiniq" in Semitic, is an example of common myths between Persian and Semitic mythology. Showing the transformation of the semantic functions of the mentioned myths during the course of time, while preserving the mystical structure, as well as the way these myths are used as one of the potential language capacities of Persian and Arabic poetry to express the political-social themes of the poet’s time are some of the requirements for doing the present research. This study has employed a descriptive-analytical method with a comparative approach. The findings of this study indicate that Nima and Adonis, in their poems, have used the myths of ''Qoqnus'' and ''Phiniq'' in a symbolic way, with a new point of similarity, different from the predecessor’s poetry, which are not only a symbol for the poets themselves, but also a way of expressing the political-social concepts they had in mind, in a way that both poets have used theses myths for a single theme and a similar mission.